PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING PADA MATA KULIAH LOGIKA DAN PENALARAN MATEMATIKA - Hartono Hartono (JPMI (Jurnal Pendidikan Matematika Indonesia), 2019)
This study aims to determine the application of the learning model of blended learning in the subjects of Mathematical Logic and Reasoning. Specific objectives are Mathematics learning achievement after the learning model of blended learning was applied in the subjects of Mathematical Logic and Reasoning and the magnitude of the increase in mathematics learning achievement after the learning model of blended learning was applied in the subjects of Logic and Mathematical Reasoning. The research method used was experimental research with a pre-experimental design and one group pretest-posttest design. The results of this research are the application of learning model of blended learning in the subject of mathematical logic and reasoning giving an increase in student learning achievement. It can be concluded that student learning achievement before being given the learning model of blended learning is classified as less, namely 52. Student achievement after being given the learning model of blended learning is good, namely 72 The results of hypothesis testing also obtained an increase in student learning achievement after being given a model of blended learning in the subjects of mathematical logic and reasoning and increasing student learning achievement after being given a model of blended learning in the material of mathematical logic and reasoning of 1.132 which is high.